The role of notch signaling pathway and non-coding RNAs in cancer and inflammation: progress, therapeutic insights, and future directions - Nie, Rong-Zu; Wang, Hang; Wang, Shuang-Shuang; Chen, Chen; Luo, Huo-Min; Zhang, Hao-Kun; Jing, Zhao-Hui; Li, Pei-Feng (Frontiers in Immunology, 2025)
The Notch signaling pathway and non-coding RNAs (ncRNAs) play significant roles in regulating key cellular processes such as cancer progression, metastasis, and drug resistance. This article systematically reviews the interactions between the Notch pathway and ncRNAs including miRNAs, lncRNAs, and circRNAs, as well as their overall impact on cancer biology. We focus on the latest research progress on how ncRNAs regulate the Notch pathway through transcriptional regulation, post-transcriptional modifications, and epigenetic mechanisms, and discuss how such interactions affect tumor microenvironment shaping, immune escape mechanisms, and treatment sensitivity. Additionally, this article deeply analyzes potential therapeutic strategies targeting the Notch-ncRNA axis, including its prospects for synergistic application with chemotherapy, radiotherapy, and immunotherapy. By integrating multi-cancer experimental data, we propose individualized diagnosis and treatment strategies based on tumor-specific Notch pathway and ncRNA expression patterns.